Chemical Composition of Essential Oils from Aerial Parts of Sisymbrium Irio from Jordan - Mahmoud A. Al-Qudah; Musa H. Abu Zarga (E-Journal of Chemistry)
The volatile compounds obtained from Sisymbrium irio growing in Jordan has been analyzed by GC-MS. The major constituents are dioctyladipate (25.44%), N-(n-proyl) acetamide (14.77%), isopropyl isothiocyanate (11.55%), isobutyl isothiocyanate (6.75%), 3,7,11,15-tetramethyl-2-hexadecen-1-ol (6.52%),cis-8,11,14-eicosatrienoic acid (6.30%), heptacosane (3.89%), palmitic acid (3.45%),n-butyl isothiocyanate (2.85 %) and dimethoxyacetophenone (2.54 %).